PENGAMATAN DAYA HITOUP BUI ASAM YANG BERASAL DARI KOTORAN TERNAK SAPI DIPADANG SAVANA BESIPAE, NTT - Albertus Husein Wawo (BERITA BIOLOGI, 1998)
Tamarind as tropical plant that grow well in dry land area and savannah. The use of tamarind product have been known as raw material for spices, drinks industries, and medicine, so that this plant is assumed very important for community in dry land area.In Besipae Savannah,South Amanuban,East Nusa Tenggara, tamarind grow wild in savannah and it is one of the sources income forpoeple in that area. During the dry season savannah produce less of fresh forages therefore the fresh leaves of tamarind are used as fodder.The function of cow dung as seed access especially as tamarind, acacias and leucaena seeds were not accomplished yet.The objectives of this study was the viability of tamarind seeds which were collected from cowdung in Besipae Savannah,South Amanuban, East Nusa Tenggara. This study was designed according to factorial model in Completely Rendomized Design(CRD), with four replications.The result of this study indicated that tamarind seeds which were collected from cowdung have higher germinatioan rate and percentage of germination compare to pure seeds from pods.Seedling growth of tamarind seeds which were collected from cowdung were better than that of seedling growth of pure tamarind seeds from pods. Application of cowdung and Bobonaro clay for germination media showed that Bobonaro clay was better than that of cowdung.